The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.brainres.2009.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional activity are accompanied with changes in inter-regional connectivity during 4 weeks motor learning

Abstract: Structural equation modeling (SEM) and fMRI were used to test whether changes in the regional activity are accompanied by changes in the inter-regional connectivity as motor practice progresses. Ten healthy subjects were trained to perform finger movement task daily for 4 weeks. Three sessions of fMRI images were acquired within four weeks. The changes in inter-regional connectivity were evaluated by measuring the effective connectivity between the primary motor area (M1), supplementary motor area (SMA), dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
88
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 106 publications
19
88
0
3
Order By: Relevance
“…basal ganglia increased with practice (Ma et al, 2010). However, with the present design, we cannot single out any particular component of the activated network as being responsible for the potential clinical benefits.…”
Section: Discussionmentioning
confidence: 98%
“…basal ganglia increased with practice (Ma et al, 2010). However, with the present design, we cannot single out any particular component of the activated network as being responsible for the potential clinical benefits.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Stevens et al (69) reported stronger coupling between the inferior frontal gyrus and face-preferential areas of the visual cortex after a face-recognition task, as well as stronger coupling between the inferior frontal gyrus and scene-specific visual areas after a scene-recognition task. Ma et al (70), using independent component analysis after extended motor-sequence learning, showed increased strength in three motor-related components, which tracked behavioral improvement. A recent study by Mackey et al (71) reported strengthened correlations between frontal and parietal attention and control regions in subjects who completed a lengthy preparation course for a law-school entrance examination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that inter-regional brain connectivity can change rapidly after just one session of motor practice (Wu et al, 2008), and then evolve gradually over the next few days (Song et al, 2011), and may last for several weeks (Ma et al, 2010). Functional connectivity has been shown to predict how well an individual learns cognitive or motor tasks (Henson et al, 1999;Wu et al, 2008) and may index functional decline as a result of aging (Cook et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We examined functional connectivity with respect to DLPFC and PMd in older and younger adults during the retrieval of motor sequences learned under interleaved compared with those learned under RP. Given that the strength of brain functional connectivity is a function of learning (Ma et al, 2010), we hypothesized that practice under CI conditions may increase prefrontal and premotor connectivity with other brain regions, which in turn, enhances retrieval of sequences. Through the PPI analysis, we found that older and younger adults relied on different patterns of functional connectivity for this benefit.…”
mentioning
confidence: 99%